Wacana Gender Dalam Perjanjian Pernikahan Rifā'ah Rāfi’ Al-Ṭahṭāwī - Rangga Hafidin (An-Nahdah Al-'Arabiyah)
A marriage agreement aimed at honoring a wife was created by Rifā'ah Al-Ṭahṭāwī, addressed to his wife Karima binti Muhammad al-Fargali in the year 1839 AD. This research aims to analyze how women are portrayed in Rifā'ah al-Ṭahṭāwī's marriage agreement. The research method involves close reading using the feminist stylistics theory by Sara Mills to analyze discourse. This feminist stylistics analysis operates on three levels: word level, phrase/sentence level, and discourse level. The results of this research indicate that at the word level, Al-Ṭahṭāwī uses deviations from neutral vocabulary to derogatory terms for women. At the phrase/sentence level, the study indicates that the sentence constructions made by Al-Ṭahṭāwī contribute to marginalizing the role of women in the presence of men. Then, at the discourse level, Al-Ṭahṭāwī constructs the text to involve women in accepting the consequences of the agreement.